The rapid size- and shape-controlled continuous hydrothermal synthesis of metal sulphide nanomaterials - Dunne, Peter W.; Starkey, Christopher L.; Gimeno-Fabra, Miquel; Lester, Edward (Royal Society of Chemistry, 2014)
Continuous flow hydrothermal synthesis offers a cheap, green and highly scalable route for the preparation of inorganic nanomaterials which has predominantly been applied to metal oxide based materials. In this work we report the first continuous flow hydrothermal synthesis of metal sulphide nanomaterials. A wide range of binary metal sulphides, ZnS, CdS, PbS, CuS, Fe₍₁₋ᵪ₎S and Bi₂S₃, have been synthesised. By varying the reaction conditions two different mechanisms may be invoked; a growth dominated route which permits the formation of nanostructured sulphide materials, and a nucleation driven process which produces nanoparticles with temperature dependent size control. This offers a new and industrially viable route to a wide range of metal sulphide nanoparticles with facile size and shape control.